Nonrecurrent laryngeal nerve: A rare but predictable variation - Deepak Janardhan; Shirish Patil; Shaji Thomas; Sandeep Suresh (Journal of the Scientific Society, 2019)
A 40-year-old female was evaluated for left thyroid swelling and after left hemithyroidectomy (p T2 N0M0) with intermediate risk as per the American Thyroid Association Guidelines was referred for completion thyroidectomy as the final histology was papillary carcinoma. A contrast-enhanced computed tomographic evaluation of the neck was done which revealed a suspicious nodule in the right lower pole of the thyroid gland, and a mention of the anomalous right subclavian artery was reported. Intraoperative findings were confirmed.